2023
DOI: 10.3389/fimmu.2023.1279603
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of necroptosis-related genes in renal ischemia-reperfusion injury

Shuai Li,
Weixun Zhang,
Xiaopeng Hu

Abstract: BackgroundOxidative stress is the primary cause of ischemia-reperfusion injury (IRI) in kidney transplantation, leading to delayed graft function (DGF) and implications on patient health. Necroptosis is believed to play a role in renal IRI. This research presents a comprehensive analysis of necroptosis-related genes and their functional implications in the context of IRI in renal transplantation.MethodsThe necroptosis-related differentially expressed genes (NR-DEGs) were identified using gene expression data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Kidney IR injury is common in renal surgery and results in acute kidney injury, chronic kidney disease, and kidney fibrosis, eventually inducing kidney dysfunction. Recent studies have revealed that the renal IR injury was mediated by activated inflammation, apoptosis, and ferroptosis . MSC therapy is widely studied due to its ability to reduce inflammation in IR areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney IR injury is common in renal surgery and results in acute kidney injury, chronic kidney disease, and kidney fibrosis, eventually inducing kidney dysfunction. Recent studies have revealed that the renal IR injury was mediated by activated inflammation, apoptosis, and ferroptosis . MSC therapy is widely studied due to its ability to reduce inflammation in IR areas.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that the renal IR injury was mediated by activated inflammation, apoptosis, and ferroptosis. 44 MSC therapy is widely studied due to its ability to reduce inflammation in IR areas. However, the efficacy of MSC therapy on IR-related diseases in clinical research is unsatisfactory, partially because it cannot effectively inhibit cell death such as ferroptosis and apoptosis.…”
Section: Discussionmentioning
confidence: 99%